Frequencies of Behavioral Problems Reported by Parents and Teachers of Hearing-Impaired Children With Cochlear Implants - Boerrigter, Merle; Vermeulen, Anneke; Marres, Henri; Mylanus, Emmanuel; Langereis, Margreet (Frontiers in Psychology, 2019)
Background: Behavioral problems such as attention and hyperactivity problems, conduct problems, withdrawn behavior, anxiety and peer problems were frequently reported in profoundly hearing-impaired (HI) children with hearing aids. Due to the positive effect of cochlear implants (CIs) on hearing and language development, a positive effect on social and emotional development was found. Despite much research in social and emotional development in CI children, there is no consensus about the frequency of behavioral problems, and studies are often based on one informant with the risk of missing behavioral problems in other contexts. Aims: The first aim of this study was to investigate the frequency of behavioral problems in children with CIs compared to a normal hearing normative sample. Additionally, the frequencies of context-related behavioral problems were compared. Finally, the relation between speech perception and language skills and the frequency of reported behavioral problems was investigated. Method: Of 71 CI children, 51% were girls and 49% were boys, and the mean age was 8.6 (SD = 3.3). Behavior was reported by parents using the Child Behavior Checklist (CBCL) and by teachers using the Teacher Report Form (TRF). Frequencies of behavioral problems were compared to a normative sample. CI children were divided into four ability level categories. Frequencies of behavioral problems were compared between the categories Results: Parents and teachers of CI children reported similar frequencies of behavioral problems to the normative sample. Parents and teachers of CI children reported similar frequencies of behavioral problems at home and at school. A significantly higher frequency of behavioral problems was reported in children with low speech perception and receptive vocabulary at school. Conclusion: The frequency of behavioral problems in children with CIs does not differ in the frequency of behavioral problems in normal hearing peers. Children with lower speech perception and language levels are more at risk of developing behavioral problems at school. Adequate speech perception and language levels are found to be protective factors for the development of behavior.